Holistic Treatment of Inflammatory Disease for the Mobility Impaired - M Laymon; K Laymon (Rheumatica Acta: Open Access - Peertechz Publications, 2023)
Background: Previous studies have demonstrated the positive impact of yoga and deep breathing exercises on overall physical wellness. The effects of deep breathing alone on metabolic rate, weight, and cholesterol management have not been studied well.  Objective: This study assessed changes in C-Reactive Protein (CRP) following a 60-day intervention of a 12-minute deep breathing program.  Methods: Sixty-six participants with a BMI >27 kg/m2 and 18 years - 70 years were enrolled in this study. Participants were assigned to either the control or intervention group in a single-blind manner. The intervention group followed the novel deep breathing program, while the control group did not modify their lifestyle or exercise. Anthropometric measurements and metabolic markers were evaluated and compared between the two groups after 60 days. Results: After 60 days, the control group exhibited a mean increase change in CRP of 3.9%. The intervention group showed a mean reduction of CRP by 25%.  Conclusion: A guided daily 12-minute-deep breathing program can lead to reductions in inflammation marker CRP even without additional lifestyle modifications or medication modifications. Further investigations are warranted to explore the effects of novel deep breathing programs on metabolic markers and elucidate the underlying mechanisms of CRP reduction.